Why do people fitted with hearing aids not wear them?. (May 2013) - McCormack, Abby; Fortnum, Heather
Abstract Objective: Age-related hearing loss is an increasingly important public health problem affecting approximately 40% of 55–74 year olds. The primary clinical management intervention for people with hearing loss is hearing aids, however, the majority (80%) of adults aged 55–74 years who would benefit from a hearing aid, do not use them. Furthermore, many people given a hearing aid do not wear it. The aim was to collate the available evidence as to the potential reasons for non-use of hearing aids among people who have been fitted with at least one. Design: Data were gathered via the use of a scoping study. Study sample: A comprehensive search strategy identified 10 articles reporting reasons for non-use of hearing aids. Results: A number of reasons were given, including hearing aid value, fit and comfort and maintenance of the hearing aid, attitude, device factors, financial reasons, psycho-social/situational factors, healthcare professionals attitudes, ear problems, and appearance. Conclusions: The most important issues were around hearing aid value, i.e. the hearing aid not providing enough benefit, and comfort related to wearing the hearing aid. Identifying factors that affect hearing aid usage are necessary for devising appropriate rehabilitation strategies to ensure greater use of hearing aids.